Determinants of Internal Migration for Tertiary Students: Structural Equation Modelling Study in Klang Valley, Malaysia - Mun, Har Wai; Hua, Neo Chee; Lin, Yun Jia; Sern, Foo Ee (Asian Development Policy Review, 2022)
In developing countries like Malaysia, internal migration from rural areas to urban centers causes an imbalance in population distribution and its subsequent negative externality. This creates an urgent need to identify factors affecting internal migration. This paper examines the determinants of internal migration on tertiary students’ decision-making within the Klang Valley, Malaysia. The dependent variable is the internal migration decision making and the independent variables are the social factor, miscellaneous factor, family factor, economic factor, and government factor. Data were collected through survey questionnaires. The Partial Least Squared type of Structural Equation Modelling is applied. Findings reveal family factors, miscellaneous factors, and social factors have significant impacts on internal migration decision-making. The economic factor has a significant relationship with social factors, while the government factor has a significant relationship with both miscellaneous and economic factors. Each factor in this study has either a direct or indirect impact on internal migration decisions.